Novel Insights Into MALAT1 Function as a MicroRNA Sponge in NSCLC - Zhou, Qinfeng; Liu, Lianfang; Zhou, Jing; Chen, Yuanyuan; Xie, Dacheng; Yao, Yinan; Cui, Dawei (Frontiers in Oncology, 2021)
Long non-coding RNA metastasis-associated lung adenocarcinoma transcript-1 (MALAT1) was initially found to be overexpressed in early non-small cell lung cancer (NSCLC). Accumulating studies have shown that MALAT1 is overexpressed in tissue or serum of NSCLC and plays a key role in the occurrence and development of NSCLC. In addition, the expression level of MALAT1 is significantly related to the tumor size, stage, metastasis and distant invasion of NSCLC. Therefore, MALAT1 could be used as a biomarker for early diagnosis, severity assessment or prognosis evaluation of NSCLC. This review describes the basic properties and biological functions of MALAT1, focuses on the specific molecular mechanism of MALAT1 as a microRNA sponge in the occurrence and development of NSCLC in recent years, and emphasizes the application and potential prospect of MALAT1 in molecular biological markers and targeted therapy of NSCLC.